2016
DOI: 10.1186/s40409-016-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial evaluation of two peptide LyeTx I derivatives modified with the chelating agent HYNIC for radiolabeling with technetium-99m

Abstract: BackgroundCurrent diagnostic methods and imaging techniques are not able to differentiate septic and aseptic inflammation. Thus, reliable methods are sought to provide this distinction and scintigraphic imaging is an interesting option, since it is based on physiological changes. In this context, radiolabeled antimicrobial peptides have been investigated as they accumulate in infectious sites instead of aseptic inflammation. The peptide LyeTx I, from the venom of Lycosa erythrognatha, has potent antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The results showed a high radiochemical purity and stability (over to 90%), up to 24 h after radiolabeling. Radiochemical purity above 90% is required since the presence of high amount of impurities leads to poor image quality, which might result in a biodistribution profile that no longer reflects the nanoparticle behavior [26,45]. …”
Section: Discussionmentioning
confidence: 99%
“…The results showed a high radiochemical purity and stability (over to 90%), up to 24 h after radiolabeling. Radiochemical purity above 90% is required since the presence of high amount of impurities leads to poor image quality, which might result in a biodistribution profile that no longer reflects the nanoparticle behavior [26,45]. …”
Section: Discussionmentioning
confidence: 99%
“…It is well described that 99m Tc-labeling reactions generate two main impurities, 99m TcO 2 and 99m TcO 4 − [24,25]. The presence, in high concentration, of these entities leads to images in poor quality that might impair the correct data interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, by using the optimized protocol described in this study less than 5% of impurities were detected indicating that 99m Tc-PTX can be used in further in vivo assays. Furthermore, the physiological pH obtained after labeling (pH = 7.4) is optimal for intravenous administration [24]. The presence of —OH groups in the polyethoxylated castor oil, a constituent of the Taxol formulation might explain the high labeling efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Further studies suggested that LyeTx I amino-terminal side is indispensable to the secondary structure conformation of the peptide, influencing its interaction with bacteria, once either the modification of LyeTx I carboxyl-terminal side (LyeTx I-K-HYNIC) or the suppression of a histidine residue in the same portion (LyeTx I-b) does not compromise its antimicrobial activity. 11,12 Recently, LyeTx I-b was formulated with carboxymethylcellulose and showed activity against a strain of Staphylococcus aureus resistant to penicillin, erythromycin, and ampicillin, acting in planktonic condition and reducing biofilm viability in 90%. Furthermore, it is very effective in the treatment of keratitis, with no signs of ocular toxicity in an in vivo eye infection model induced by the same bacterium.…”
Section: Introductionmentioning
confidence: 99%